Treatment of internal inflammatory root resorption – based on own observations - Pietrzycka, Krystyna; Pawlicka, Halina (Journal of Stomatology, 2015)
Introduction. Internal inflammatory root resorption, termed internal granuloma, is a relatively rare pathological process. Resorption is defined as the process of destruction of hard dental tissues, gingiva or alveolar ridge, but if permanent teeth are affected, it is always a pathological condition. Internal inflammatory resorption begins in the dentine from inside of the pulp chamber. It is initiated and stimulated by infected necrotic pulp located coronally in relation to the resorption cavity. The choice of therapeutic methods and the success of treatment depend on the etiology of this phenomenon, and the degree of advancement of the disease. Aim of the study. To describe four cases of the authors’ own patients treated for internal inflammatory root resorption. Conclusion. The use of modern diagnostic and therapeutic methods namely three-dimensional diagnostic radiology, endodontic techniques such as ultrasonic methods used during irrigation and thermoplastic methods of canal obturation can provide good results of treatment of this pathology.